Моделювання оптимальних місць розташування та величини потужності джерел розподіленої генерації в розподільних електричних мережах напругою 10 кВ в умовах їх експлуатації - Скрипник, А. М.; Кожан, Д. П. (Енергетика і автоматика, 2017)
SIMULATION OF OPTIMAL DO PLACEMENTS AND THE MAGNITUDE OF POWER OF SOURCES DISTRIBUTED GENERATION IN DISTRIBUTION ELECTRIC NETWORKS WITH VOLTAGE 10 kV IN CONDITIONS THEIR OPERATIONA. Skrypnyck, D. Kozhan The purpose of research – proposals on development of mathematical model of search for optimal do placements and magnitude of power of sources distributed generation in distribution electric networks with voltage 10 kV in conditions their operation.In a basis of a mathematical model of search of the optimum location of sources of the distributed generation in system of electrical power supply use of the gradient method is offered. In which elements a vector gradient are derivative of target function (not balances of the active and reactive capacities or value of the active and reactive capacities in nodes of the estimated diagram) according to the appropriate retrieval characteristics of the mode of an electrical network as which both angles, and modules of node voltages can appear.Vector - gradient determined for all nodes the settlement scheme (except center nourishment) in its maximum mode load.For determination of optimum values of the active and reactive capacities of sources of the distributed generation in the optimum place of its installation modification of a method of Newton is used. Partial matrix (matrix Jacobi) which includes derivatives for active and reactive nodal facilities to perform optimum redistribution between the centers specified power supply.Pilot studies of the above-stated offers are executed on the example of a fragment of the scheme of electric network voltage 10 kV with parameters of plots and values of nodal loading.Сonclusions1. The made experiments on introduction of one source of the distributed generation in a fragment of distributive network of 10 kV have shown a possibility of use of the offered technique.2. At the considerable volumes of distributive networks there can be a need for introduction of bigger quantity of sources of the distributed generation. However influence of a significant amount of electric parameters on the choice of the optimum locations of sources of the distributed generation and sizes of their capacities can result in need of improvement of the offered technique.